THE IMPORTANCE OF EARLY VERTICALIZATION IN PATIENTS WITH ISCHEMIC STROKE AFTER EMERGENCY ENDOVASCULAR THROMBASPIRATORY TRANSPLANT - N.B. Mirzaeva,; M.M. Bakhadirkhanov, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The study evaluates the clinical feasibility and outcomes of early verticalization in patients with ischemic stroke following emergency endovascular thromboaspiration. Conducted at the Neurology Department of the Republican Scientific Center for Emergency Medical Care (2022–2024), the research included 140 patients (41–79 years old) in the acute and subacute stages of ischemic stroke affecting the carotid and vertebrobasilar systems. The main group (n=70) underwent emergency X-ray endovascular thromboaspiration, while the comparison group (n=70) received standard therapy without intervention. The early verticalization protocol consisted of gradual elevation from 30° to 80° within ≤12 hours post-procedure, performed 2–3 times daily with continuous hemodynamic monitoring. Functional outcomes were assessed using the modified Rankin Scale (mRS) at 90 days, and neurological recovery by NIHSS at 48 hours. Results demonstrated that 92.9% of patients achieved full verticalization (80°) within the first day, with orthostatic hypotension occurring in only 8.6% of cases and no severe cardiopulmonary complications. Functionally independent recovery (mRS 0–2) at 90 days was achieved in 60.0% of the main group versus 42.9% of controls (p=0.028), with an NNT of six. Early verticalization accelerated walking initiation (3.2 ± 1.1 vs. 5.6 ± 1.8 days; p<0.001) and shortened hospitalization by nearly three days, without increasing the risk of hemorrhage (2.9% vs. 4.3%; p=0.65) or mortality (5.7% vs. 8.6%; p=0.52). These findings confirm that, when performed under a structured protocol and adequate monitoring, early staged verticalization is safe, improves neurological recovery, and reduces functional disability in ischemic stroke patients after endovascular thromboaspiration. The inclusion of early verticalization in post-reperfusion rehabilitation protocols is therefore recommended, requiring coordinated management between neurointensive, interventional, and rehabilitation teams.